Automatic detection of spring faults during assembly of reciprocating compressors - Potočnik, Primož (Strojniški vestnik, 2009)
Automatic condition monitoring application for the detection of spring faults during assembling of reciprocating compressors is presented in this paper. Spring faults are characterized by incorrect positioning of compressor body on the supporting springs. Consequently, compressors with such faults should be detected and eliminated from the production. The paper describes development and application of a condition monitoring (CM) system for the production line. The CM system is composed of a mechanical pneumatic system and a software for the analysis and detection of failures. The mechanical system is designed to push toward the body of the compressor and simultaneously measure the pressing force. Spring faults are characterized by an increased force, therefore force signals are used to extract features, appropriate for an automatic condition monitoring. The system was tested during regular production in the company, with additional sets of compressors with built-in spring faults. The main contribution of this paper is the development and testing of various decision strategies for the recognition of faulty compressors. Standard 3-sigma decision strategy is compared to optimized stationary decision strategy and two adaptive strategies: adaptive strategy with constant deviation and adaptive strategy with adaptive deviation. Results show that adaptive decision strategy with adaptive deviation yields the best fault recognition rate and is, therefore recommended for the application on the industrial production line.
Keywords: kompresorji; proizvodnja; montaža; preizkušanje; vzmeti; napake